The right of young people to participate in public and political life: some aspects - Ibrayeva, A.S.; Goncharov, S.B. (Формирование сильного и успешного государства в новой глобальной реальности: Материалы научной конференции,20 января 2016 г.("Актуальные проблемы государства и права" Вып.4, 2016)
This article was prepared within the framework of basic research in 2597 GFZ "Problems of constitutional development of Kazakhstan as a sovereign state: the past, present and future." While preparing this article the statistics as well as the data from the survey commissioned by the MES Institute of State and Law of Kazakh National University under the name of Al-Farabi, during the preparation of the National Report "Youth of Kazakhstan- 2015" were used. The sociological research was carried out in 16 regions of Kazakhstan, and over 2,200 respondents – young people aged between 14 and 29 years old - were interviewed. They also conducted the focus-group interviews of young people and experts on the youth.
Keywords: youth; youth in the work of state; electoral participation of young; youth organizations; Research Subject Categories::LAW/JURISPRUDENCE